Analysis of the Suitability of Developing Economically Valuable and Sustainable Integrated Agriculture in the Reclamation of Former Mining Lands - Deni Sri Wardana; Sri Wahyuni; Dolly Priatna (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Intensive nickel mining activities in North Morowali Utara Regency have resulted in severe environmental degradation, including soil damage, biodiversity loss, and water pollution. This study aims to analyze the impact of sustainable integrated farming development as a reclamation strategy for former nickel mining land, and to evaluate the sustainability of this system from economic, ecological, and social perspectives. The research was conducted in Molores and Molino Villages using an exploratory qualitative approach, with data collected through interviews, field observations, focus group discussions (FGDs), and Multidimensional Scaling (MDS) analysis based on the Rapfish method. The findings indicate that the implementation of integrated farming combining agriculture, livestock, aquaculture, and organic waste processing can effectively restore soil fertility, increase household income, and enhance community resilience in food and energy. The sustainability index indicated a "moderately sustainable" status, with the highest score observed in the economic dimension. This system also reduces community dependency on the mining sector and promotes active participation in environmental conservation. Sustainable integrated farming has proven to be an effective, community-based reclamation solution and is highly replicable in other post-mining areas.